Nectar Analysis Throughout the Genus Nicotiana Suggests Conserved Mechanisms of Nectar Production and Biochemical Action - Silva, Fredy A.; Guirgis, Adel; Thornburg, Robert (Frontiers in Plant Science, 2018)
We have evaluated the floral nectars of nine species from different sections of the genus Nicotiana. These nine species effectively cover the genus. We found that the nectary glands from these different species showed similar developmental regulation with swelling of nectaries during the first half of development and a distinct color change in the nectary gland as development approaches anthesis. When we examined the composition of the nectar from these nine different species we found that they were similar in content. Carbohydrate compositions of these various nectars varied between these species with N. bonariensis showing the highest and N. sylvestris lowest level of sugars. Based upon the amount of carbohydrates, the nectars fell into two groups. We found that hydrogen peroxide accumulated in the nectars of each of these species. While all species showed the presence of hydrogen peroxide in nectar, the quantitative amounts of hydrogen peroxide which was very high in N. rustica and N. bonariensis, suggesting be a common characteristic in short flower Nicotiana species. We further found that the antioxidant ascorbate accumulated in nectar and β-carotene accumulated in nectaries. β-carotene was most high in nectaries of N. bonariensis. We also examined the presence of proteins in the nectars of these species. The protein profile and quantities varied significantly between species, although all species have showed the presence of proteins in their nectars. We performed a limited proteomic analysis of several proteins from these nectars and determined that each of the five abundant proteins examined were identified as Nectarin 1, Nectarin 3, or Nectarin 5. Thus, based upon the results found in numerous species across the genus Nicotiana, we conclude that the mechanisms identified are similar to those mechanisms found in previous studies on ornamental tobacco nectars. Further, these similarities are remarkably conserved, throughout the genus Nicotiana.